Differential toxicity of ataxin-3 isoforms in Drosophila models of Spinocerebellar Ataxia Type 3. - Johnson, S.L.; Blount, J.R.; Libohova, K.; Ranxhi, B.; Paulson, H.L.; Tsou, W.L.; Todi, S.V. (Neurobiology of Disease, 2019)
The most commonly inherited dominant ataxia, Spinocerebellar Ataxia Type 3 (SCA3), is caused by a CAG repeat expansion that encodes an abnormally long polyglutamine (polyQ) repeat in the disease protein ataxin-3, a deubiquitinase. Two major full-length isoforms of ataxin-3 exist, both of which contain the same N-terminal portion and polyQ repeat, but differ in their C-termini; one (denoted here as isoform 1) contains a motif that binds ataxin-3's substrate, ubiquitin, whereas the other (denoted here as isoform 2) has a hydrophobic tail. Most SCA3 studies have focused on isoform 1, the predominant version in mammalian brain, yet both isoforms are present in brain and a better understanding of their relative pathogenicity in vivo is needed. We took advantage of the fruit fly, Drosophila melanogaster to model SCA3 and to examine the toxicity of each ataxin-3 isoform. Our assays reveal isoform 1 to be markedly more toxic than isoform 2 in all fly tissues. Reduced toxicity from isoform 2 is due to much lower protein levels as a result of its expedited degradation. Additional studies indicate that isoform 1 is more aggregation-prone than isoform 2 and that the C-terminus of isoform 2 is critical for its enhanced proteasomal degradation. According to our results, although both full-length, pathogenic ataxin-3 isoforms are toxic, isoform 1 is likely the primary contributor to SCA3 due to its presence at higher levels. Isoform 2, as a result of rapid degradation that is dictated by its tail, is unlikely to be a key player in this disease. Our findings provide new insight into the biology of this ataxia and the cellular processing of the underlying disease protein.